ASUPAN ENERGI, SENG DAN MAGNESIUM YANG TIDAK SESUAI KEBUTUHAN SEBAGAI FAKTOR RISIKO PREEKLAMPSIA DI DAERAH PAPARAN PESTISIDA TINGGI - Rifatul Masrikhiyah (Jurnal Pangan dan Gizi, 2018)
Pre-eclampsia is a cause of death maternal mortality highest in Brebes district (42 %). The cause of pre-eclampsia unknown certainly, Oxidative stress is the one cause of pre-eclampsia. The aimed of this study was to analyze macro and micronutriens intake which are unjustified with the needs as pre-eclampsia risk factors. The research is observational research with design case control. Subjects in the study was mother post partum (20-35 years) which consists of 55 cases (pre-eclampsia) and 55 control (not pre-eclampsia). Nutrient intake was measured by semi quantitative food frequency questionnaires and data MUAC, BMI, Age and education was collected from interviews structured. Data was analyzed by counting odds ratio and method of logistic regression. There was no difference in age and LILA between the cases and control group. The cases had median of long education lower than control. The cases had median of BMI higher than control. Low Magnesium intake (OR = 16,011; 95%CI : 4,886 – 52,463) and low zinc intake (OR = 10,925; 95%CI : 2,633 – 45,335) were pre-eclampsia risk factor in high pesticide exposure area.